YOUTH POLITICAL IDENTITIES IN EMERGING POPULAR SECTORS IN A CONTEXT OF INFORMALITY AND TRANSGRESSION - TICONA FERNÁNDEZ-DÁVILA, Rubén (2021)
Since 1990 - 2020 informality and precariousness have deepened in Peruvian society, transforming not only the economic field but also the ways of thinking and doing politics. In this sense, the new popular political identity is redefined from new historical coordinates: neoliberalism, informality and precariousness in a cultural context marked by the expansion of transgression give rise to new sensibilities, values and aspirations of a new political individual who today it finds a new form of expression and political representation. The objective of the article is to analyze the new youth political identities that are emerging in the popular sectors. The methodology used has been qualitative, 16 in-depth interviews were conducted inSan Juan de Lurigancho in 2019.